Perspectives on Adult Learning: Framing Our Research - Rosemary S. Caffarella; Sharan B. Merriam (Adult Education Research Conference, 1999)
Based on a review of the literature we describe the assumptions and salient concepts of two major perspectives on adult learning: the individual and the contextual. We then argue that although research should continue to be grounded in these two perspectives, we should expand our research efforts in a third paradigm consisting of an integration of these two perspectives.